Uncommon but Important: Tertiary Center Experience with Rare Cases of Breast Hamartoma - Mihaela Camelia Tîrnovanu; Bogdan Florin Toma; Elena Cojocaru; Elena Țarcă; Ștefan Dragoș Tîrnovanu; Vlad Gabriel Tîrnovanu; Cristian Mârțu; Roxana Ana Covali; Anca Irina Gradinariu; Gabriela Ghiga; Ludmila Lozneanu (Life)
Background: A breast hamartoma or fibroadenolipoma is a rare, benign mass consisting of disorganized mature breast tissue elements. Surgical excision is recommended if the lesion exhibits rapid progressive growth. However, incomplete excision may result in recurrence. The objective of this study is to provide comprehensive insights into the characteristics of breast hamartomas and to conduct a thorough investigation into their clinical presentation, diagnostic procedures, and management strategies. Methods: We report on 13 cases of breast hamartomas treated surgically between January 2018 and June 2023 at the Obstetrics and Gynecology Hospital “Cuza Vodă” in Iași. We analyzed their histological images and immunohistochemical evaluations. Results: The mean age of the patients was 33.35 years, ranging from 22 to 57 years. Clinically, all patients presented with a painless mass. The diagnosis was confirmed through ultrasound examination, which revealed that hamartomas appeared as well-circumscribed, oval, and heterogeneous in echotexture. The tumor sizes ranged from 1 to 17 cm, with an average size of 6.75 cm. Surgical treatment involved lumpectomy with the excision of a small portion of normal tissue surrounding the tumor. The histological variability of these tumors poses diagnostic challenges for pathologists, potentially leading to underdiagnosis. Conclusions: Most hamartomas exhibit characteristic features on ultrasound attributable to their fibrous, glandular, and adipose tissue composition. Accurate identification of hamartomas is crucial due to the potential for recurrence. Notably, none of the women in our study experienced recurrence during the follow-up period.